Challenge of Human Resource Management in Virtual Organization-Survey Relationship between Degree of Virtualization and Organizational Commitment - Hassan Abedjafari; Mona Jamporazmey; HaniehSadat Beiryaie (Journal of Information Technology Management)
In the business environment, virtual organizations can meet market needs efficiently and effectively via knowledge worker and high flexibility and also generate significant competitive advantage. Due to obtaining the advantage of these organizations, managerial issues related to them must be recognized and organized. Decrease of face to face relationship, geographically distributed, dynamic job environment introduce human resource management as a challenging and complicated matter. Low organizational commitment and high rate of job turn around are instances of problems of human resource domain in virtual organizations. The purpose of this research is to investigate whether there is a significant relation between degree of virtualization and organizational commitment by adopting Allen & Meyer‘s model for conceptualization of commitment and Bauer& Koszgi’s model for measuring virtualization which has not been applied in this matter yet. Finally, this paper will explore the notion that there is a significant and negative relation between degree of virtualization and organizational commitment.